Room-temperature scavengers for macromolecular crystallography: increased lifetimes and modified dose dependence of the intensity decay. - Barker, A; Southworth-Davies, R; Paithankar, K; Carmichael, I; Garman, E (2009)
The advent of highly intense wiggler and undulator beamlines has reintroduced the problem of X-ray radiation damage in protein crystals even at cryogenic temperatures (100 K). Although cryocrystallography can be utilized for the majority of protein crystals, certain macromolecular crystals (e.g. of viruses) suffer large increases in mosaicity upon flash cooling and data are still collected at room temperature (293 K). An alternative mechanism to cryocooling for prolonging crystal lifetime is the use of radioprotectants. These compounds are able to scavenge the free radical species formed upon X-ray irradiation which are thought to be responsible for part of the observed damage. Three putative radioprotectants, ascorbate, 1,4-benzoquinone and 2,2,6,6-tetramethyl-4-piperidone (TEMP), were tested for their ability to prolong lysozyme crystal lifetimes at 293 K. Plots of relative summed intensity against dose were used as a metric to assess radioprotectant ability: ascorbate and 1,4-benzoquinone appear to be effective, whereas studies on TEMP were inconclusive. Ascorbate, which scavenges OH* radicals (k(OH) = 8 x 10(9) M(-1) s(-1)) and electrons with a lower rate constant (k(e-(aq)) = 3.0 x 10(8) M(-1) s(-1)), doubled the crystal dose tolerance, whereas 1,4-benzoquinone, which also scavenges both OH* radicals (k(OH) = 1.2 x 10(9) M(-1) s(-1)) and electrons (k(e-(aq)) = 1.2 x 10(10) M(-1) s(-1)), offered a ninefold increase in dose tolerance at the dose rates used. Pivotally, these preliminary results on a limited number of samples show that the two scavengers also induced a striking change in the dose dependence of the intensity decay from a first-order to a zeroth-order process.